ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK BADAN (Studi Empiris Pada Wajib Pajak Badan Yang Terdaftar Di Kantor Pelayanan Pajak Madya Semarang) - Budi Setiawan, 12.05.52.0248; Kartika, Andi (Students Journal of Accounting and Banking, 2015)
This Study aims to examine and analyze the effect of a tax professional attitude, intention professional tax, financial condition, corporate facilities, and organizational climate on tax payer compliance at companies listed in the KPP Madya Semarang either partially or simultaneously. The Study population was the entire tax professional who work in companies that exist in semarang as many as 995, while the sample qualified as many as 113 people as respondents. The process of collecting data from respondents conducted by distributing quesionaire to 130 corporate taxpayers with incidental sampling technique. Test instruments used are validity and reability. Based on the result of the study can be summarized as follows: (1) attitude towardstaz compliance professional tax positive effect on Tax Compliance Agency Significantly, (2) the intention to behave obediently professional taz positive effect on Tax Compliance Agency Significantly, (3) the financial condition of a positive effect on tax Compliance Agency significantly, (4) positive effect on the companyâs facilities Tax Compliance Agency significantly, (5) organizational climate positive effect on Tax Compliance Agency significantly.Keywords: Taxpayer compliance